2022
DOI: 10.1093/qje/qjac024
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Discrimination Among Large U.S. Employers

Abstract: We study the results of a massive nationwide correspondence experiment sending more than 83,000 fictitious applications with randomized characteristics to geographically dispersed jobs posted by 108 of the largest U.S. employers. Distinctively Black names reduce the probability of employer contact by 2.1 percentage points relative to distinctively white names. The magnitude of this racial gap in contact rates differs substantially across firms, exhibiting a between-company standard deviation of 1.9 percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(39 citation statements)
references
References 79 publications
2
37
0
Order By: Relevance
“…The percentage of the population that identifies as Asian, Latino, and Black American have all increased substantially in recent decades (e.g., Jones et al, 2021). Moreover, Asian, Latino, and Black Americans all face higher levels of discrimination relative to White Americans across a variety of domains including hiring, which was the focus of the present investigation (e.g., Kline et al, 2022; R. T. Lee et al, 2019, Lippens et al, 2023; Quillian et al, 2017, 2020).…”
Section: The Prototype Model Of Atdsmentioning
confidence: 98%
“…The percentage of the population that identifies as Asian, Latino, and Black American have all increased substantially in recent decades (e.g., Jones et al, 2021). Moreover, Asian, Latino, and Black Americans all face higher levels of discrimination relative to White Americans across a variety of domains including hiring, which was the focus of the present investigation (e.g., Kline et al, 2022; R. T. Lee et al, 2019, Lippens et al, 2023; Quillian et al, 2017, 2020).…”
Section: The Prototype Model Of Atdsmentioning
confidence: 98%
“…2 Name-based microaggressions are not restricted to K-12 experiences, however. They have been found to influence mental health service provision, 3 job interview call-backs, [4][5][6] and physician wellness. 7 A 2020 report by the Migration Policy Institute found that 17% of all health care workers are foreign born-comprising 29% of physicians, 16% of nurses, and 22% of nursing assistants.…”
Section: What Does Your Name Mean To You?mentioning
confidence: 99%
“…Recent research on hiring discrimination in several countries, includes Canada (Oreopoulos (2011)), China (Maurer-Fazio (2012)), and Mexico (Arceo-Gomez and Campos-Vazquez (2014)). Discrimination attributes studied include age (David, Ian and Button (2019), Burn et al (2022)), unemployment spells (Kroft, Lange and Notowidigdo (2013)), gender (Haoran He and Han (2023)), and race Kline, Rose and Walters (2022).…”
Section: Introductionmentioning
confidence: 99%